Pigmentation Lesions and Salivary Flow Rates on Woman Smokers: Lesi Pigmentasi dan Laju Aliran Saliva pada Wanita Perokok - Fatimah, Aulia; Tjahajawati, Sri; Razali, Ervin (TALENTA, 2019)
Smoking habit has many negative effects towardswomen’s systemic and oral health. One of them are decrease of salivary flow rate and an appearance of pigmentation lesion in gingiva. The aim of this research is to obtain data regarding salivary flow rate and pigmentation lession on women smokers.This descriptive research used 50 samples by simple random sampling method. The salivary flow rate data was obtained by spitting method and the pigmentation lesion data was described by visual method. The other data wasobtained through filling the questionnaire. By the findings of this research, it was found that the mean value of salivary flow rate and pigmentation lession of women smokerswho consumed1-8 cigarettes per day for 1-2, 2-5 and > 5 years were 0.4 ml/min & 51,7%, 0.4 ml/min & 100%, 0.4 ml/min & 100%. The mean value of salivary flow rate and pigmentation lession of women smokerswho consumed9-16 cigarettesper day for 1-2, 2-5 and > 5 years were 0.4 ml/min & 100%, 0.4 ml/min & 100%, 0.4 ml/min & 90%. The mean value of salivary flow rate and pigmentation lession of women smokerswho consumed>16 cigarettes per day for 1-2, 2-5 and > 5 years were 0.3 ml/min & 100%, 0.2 ml/min & 100%, 0.2 ml/min & 100%. The conclusion shows that salivary flow rate on women smokers has a lower value compared to normal salivary flow rate or its called oligosialia and most of the subjects have